Nutritional hematic parameters and presence of parasitic infection in children from an urban environment in La Plata, Argentina - Minvielle, Marta Cecilia (2016)
The objective was to evaluate the levels of hematic parameters of nutrition and frequency of parasitic infections in children from La Plata, province of Buenos Aires, in the central region of Argentina. Hemoglobin, calcium and magnesium levels and presence of antitoxocara antibodies and intestinal parasites were determined. Parents were informed about the study and they were requested to give their informed consent and to be present at the moment of blood extraction. Protocols developed were approved by the Universidad Nacional de La Plata. Anemia occurred in 19.2% of 183 children. In the group 3- to 5-yearold children it was more frequent that among the 6- to 12-year-olds (p= 0.0031). Low calcium and magnesium levels occurred in 71.6% and 9.9% of the subjects, respectively. 15.9% of the children were seropositive for toxocariasis and 74.4% registered intestinal parasitosis. Children 6 to 12 years old were more infected than younger children, 80.0% and 64.7% (p= 0.0243). Some authors relate parasitic infections with nutritional disorders in infected children. However, other authors report controversy over this connection. In our study, no relationship between parasite-infected children and presence of anemia and/or reduced levels of calcium in blood was observed, which strengthened the dietary origin of the nutritional situation of schoolchildren.